Approaches to financing public benefit organisations in the area of national security in the digital environment - Oliński, Marian (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
Nonprofit organisations, operating in various fields and fulfilling diverse functions, play a significant role in civil society. One of the specific types of nonprofit organisations are public benefit organisations. Therefore, the aim of the research presented in this article is to identify the revenue generation mechanisms used by public benefit organisations operating in the area of national security (i.e., public order and safety, national defense and the activity of the Armed Forces of the Republic of Poland, and rescue systems and protection of residents). As part of the research procedure, financial and substantive reports of public benefit organisations, as well as their websites, were analyzed. The research identified the sources of revenue for public benefit organisations, as well as the degree of diversification of the revenue generation mechanisms in the online environment. The article demonstrates that a greater number of the revenue generation mechanisms utilized by public benefit organisations is accompanied by an increase in revenue. Moreover, organisations that obtain more money from private sources also use a larger number of revenue generation mechanisms in the online environment.